PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN PPKN MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN GROUP INVESTIGATION (GI) - Kemal Pasha; Oksiana Jatiningsih; Rachmad Suyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research uses a Problem-Based Learning (PBL) learning model with a Group Investigation (GI) approach to improve students' critical thinking skills in class X PPKn learning at SMKN 3 Surabaya. Research objectives 1) to determine students' critical thinking in implementing the Problem-Based Learning (PBL) learning model with the Group Investigation (GI) approach in the PPKn subject of X Machine 2 students at SMK 3 Negeri Surabaya. 2) To explain the Problem-Based Learning (PBL) learning model with the Group Investigation (GI) approach in PPKn subjects which can improve the critical thinking of X Machine 2 students at SMK 3 Negeri Surabaya. The type of research is classroom action research. Data collection techniques using observation, interviews, tests, and documentation. The results of the research showed that the results of students' activities in cycles I and II achieved an average result of 50% and 87%. The results of the critical thinking observation sheet when carrying out learning cycles I and II achieved observation results of 54% and 84%. Based on the assessment of student learning outcomes for cycles I and II that were applied, the results were an average of 70 with a completion level criterion of 56%. Meanwhile, in Cycle II there was an increase with an average of 88 students with a completion level criterion of 92%. The Problem-Based Learning (PBL) learning model with the Group Investigation (GI) approach can improve students' critical thinking skills in class X PPKn learning at SMKN 3 Surabaya.